2019
DOI: 10.1177/1457496919832150
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Prognostic Factors and Recurrence Patterns After Curative-Intent Resection of Perihilar and Distal Cholangiocarcinomas

Abstract: Background: Perihilar cholangiocarcinoma and distal cholangiocarcinoma arise from the same tissue but require different surgical treatment methods. It remains unclear whether these cholangiocarcinoma types have different outcomes, prognostic factors, and/or recurrence patterns. Methods: This retrospective study evaluated patients who underwent curative-intent resection for perihilar cholangiocarcinoma or distal cholangiocarcinoma at a tertiary academic hospital during 2000–2015. Survival and prognostic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(34 reference statements)
2
7
0
Order By: Relevance
“…The 90-day mortality rates reported in the literature range between 3% and 8%, 5 , 9 , 11 , 12 , 14 16 which is comparable with our findings. Extended resections, with or without vascular resection, are certainly relevant risk factors for morbidity and mortality but may be necessary to achieve complete tumor removal.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The 90-day mortality rates reported in the literature range between 3% and 8%, 5 , 9 , 11 , 12 , 14 16 which is comparable with our findings. Extended resections, with or without vascular resection, are certainly relevant risk factors for morbidity and mortality but may be necessary to achieve complete tumor removal.…”
Section: Discussionsupporting
confidence: 92%
“…Firstly, a positive resection margin is an independent risk factor for worse survival, as already shown by previous studies. 3 , 17 , 11 , 14 , 16 The strong impact of a >1mm tumor clearance that was shown by transferring the Leeds protocol for histopathological PDAC workup to DBC underlines the importance of radical surgical approaches in order to achieve this goal. 32 Secondly, intraoperative blood loss showed an even more pronounced effect on OS and should therefore be minimized, especially when extended resections are performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, each subtype is now considered to have different tumor biology and prognosis [8]. Beyond that, a 15-year study also demonstrated different patterns of initial recurrence between patients with hilar cholangiocarcinoma and DCCA [21]. Ghiassi-Nejad et al [18] analyzed the recurrence pattern of 145 patients with cholangiocarcinoma, including 102 cases of intrahepatic bile duct cancer and 43 cases of hilar cholangiocarcinoma.…”
mentioning
confidence: 99%
“…In a Mayo Clinic cohort of patients, the median OS of DCCA was 22.0 months [25]. In V. Sallinen's study, the OS of DCCA patients was 40.4 months (95% CI: 19.1-61.7 months) [26]. In the study of Zhou WW et al, the median OS of all patients was 45.5 months (95% CI 13.5-77.5 months), and the 1-year, 3-year, and 5-year OS rates after resection were 82.6%, 55.2%, and 47.2%, respectively [27].…”
Section: Surgerymentioning
confidence: 93%